Treated phosphogypsum as an alternative set regulator and mineral addition in cement production. (20th January 2020) - Rosales, J.; Pérez, S.M.; Cabrera, M.; Gázquez, M.J.; Bolivar, J.P.; de Brito, J.; Agrela, F.
Abstract: Various treatments of phosphogypsum samples extracted in Huelva, Spain, curing conditions and incorporation ratios were studied to evaluate the viability of being used as set regulator or as supplementary cementitious material to improve the mechanical behaviour of cement mortars. The physical-chemical properties, mechanical behaviour and environmental impact of these phosphogypsum-based cement mortars were determined. It was concluded that the phosphogypsum treatments and curing conditions influence the mineralogical transformations of mortars and therefore also the mechanical behaviour of the mortars tested. Furthermore, the heavy metal impurities in the phosphogypsum were immobilized in the cement matrix, leading to a clear improvement of the technical properties of cement mortars made with this waste compared to the traditional use of natural gypsum. Graphical abstract: Image 1 Highlights: Different treatments of phosphogypsum (PG) were performed to improve it. The potential utilization of PG as mineral addition and setting time regulator was evaluated. The curing conditions and the PG content affect to the minerals phase and mechanical behaviour of cement mortars. PG may be used as a substitute of natural gypsum improving the chemical and mechanical properties of cement mortars.